1998
DOI: 10.1094/phyto.1998.88.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Oxidation inBotrytis cinereaConidia

Abstract: Observations using light microscopy showed that approximately 30% of Botrytis cinerea conidia treated with semi-lethal concentrations (i.e., 60 mug/ml) of the grapevine phytoalexin resveratrol possessed intracellular brown coloration. This coloration was never observed in the absence of resveratrol or in conidia treated with resveratrol together with sulfur dioxide (antioxidant compound) or sodium diethyldithiocarbamate (inhibitor of laccase action), suggesting that discoloration resulted from the laccase-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…In presence of the diterpenoids, the appearance of cytological abnormalities was not observed (data not shown). This result was different to those obtained with resveratrol, a natural phytoalexin; since it has been reported that this compound produced curved germ tubes and cytological abnormalities in B. cinerea conidia 18 . It is important to emphasize that this is the first work in which the antifungal effect against the fungus B. cinerea of two epimers was compared.…”
Section: Antifungal Activity Of Diterpenoids On B Cinereacontrasting
confidence: 95%
“…In presence of the diterpenoids, the appearance of cytological abnormalities was not observed (data not shown). This result was different to those obtained with resveratrol, a natural phytoalexin; since it has been reported that this compound produced curved germ tubes and cytological abnormalities in B. cinerea conidia 18 . It is important to emphasize that this is the first work in which the antifungal effect against the fungus B. cinerea of two epimers was compared.…”
Section: Antifungal Activity Of Diterpenoids On B Cinereacontrasting
confidence: 95%
“…98 The effect of an attack with Botrytis cinerea as a biotic stress factor 99 infl uenced apparently higher content in the year 2001. Lesser content in the skins in comparison with the seeds could be caused by its metabolization 100 and by the fact that only free trans-resveratrol was determined. Higher levels of trans-resveratrol were found in blue varieties as compared with white ones, 11 because resveratrol is more sensitive to oxidation in white musts.…”
Section: Effect Of Grape/vine Varieties and Cultivarsmentioning
confidence: 99%
“…The ability of B. cinerea to infect grapevine has been associated with its capacity to degrade stilbene phytoalexins. Laccase-mediated oxidation of resveratrol by a number of enzymes has been described (Adrian et al, 1998). Resveratrol have been also recognized as phytoalexin produced by Arachis and Trifolium (Leguminosae) and, Broussonetia (Moraceae), Festuca, Saccharum (Gramineae) and Veratrum (Liliaceae) (reviewed in Grayer and Harborne, 1994).…”
Section: In Response To Infection For Some Fungi Such Asmentioning
confidence: 99%